Efeitos da condução da política monetária na economia brasileira pós-Plano Real - Carvalho, Leandro Vinícios (Universidade Federal de São Carlos, 2012)
This paper aimed to analyze the dynamics of the evolution of interest rates in Brazil from the period after the Real Plan. It will take place throughout the dissertation a study on the adoption and operation of the system of inflation targets, as well as the functioning and organization of the National Financial System. It will be discoursed on the implementation of monetary policy by the Central Bank and also a study made of the main theoretical discussions regarding the adoption of monetary policy regime of inflation targeting. In addition, there will be an explanation of some studies that investigated empirically the effects of monetary policy on economic variables after the adoption of inflation targeting. To evaluate the effects of maintaining interest rates at high levels will be estimated using the methodology of the Vector Error Correction, the model of monetary transmission specified by Bogdanski et al. (2000), where you can analyze the behavior of variables such as income (output gap), the exchange rate, inflation and risk premium, compared to the nominal interest rate (Selic). The estimated unrestricted model (variation of the model proposed by Bogdanski et al. (2000)) showed evidence that the Selic rate, the output gap and inflation are related as expected in the target system, the basic interest rate uses the level of economic growth (gap) as an indicator of the growing economy in order to maintain stable price levels. There was also the conclusion that there is room for reduction in interest rates between the years 2012 and 2013, albeit sparingly, to levels lower than current (between 9.0% and 10%) in order to generate a stimulus to the growth of domestic investment, since they do not commit to maintaining inflation at low levels and controlled.
Effects of the Conduct of Monetary Policy on the Brazilian Economy in Post-Real Plan.
Keywords: política monetária; inflação - Brasil; taxa de juros; inflation target; selic; monetary transmission; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA MONETARIA E FISCAL